MISKONSEPSI SISWA PADA MATERI LISTRIK STATIS DI KELAS XII SMA NEGERI 9 PONTIANAK - Daniati, Sapitri; Djudin, Tomo; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to find the profile of student misconception and to see the difference in percentage of misconception of male and female students of grade XII of SMA Negeri 9 Pontianak on static electricity material, using descriptive research method. The data collection technique uses multiple choice test with an open reason. An average student misconception 77,36% of 90 students found. 65 (72.22%) students assumed that if two objects were rubbed together then electrons and protons shifted. 78 (86.88%) students assume if the charge of an object after rubbing has excess electrons then the charge of the object initially is negative. 18 (20%) students assume the interaction of two objects of mutual excess electrons will pull. 80 (88.89%) students assume large electric force inversely proportional to the distance between charged objects. In Problems 5 and 6, 100% of students assume that the force of attraction or deny between two charged objects is due to the amount of charge on the object. 42 (46.67%) students on problem 7, and 78 (86.67%) students on question 10 assume the positive source charge of the direction of the field near the source charge and the negative source charge of the field direction away from the source load. In problem 8, 70 (77.78%) misconception students explain the electric field strength at a point. 86 (95.56%) students assume the distance of an object, the stronger the field strength. There is no difference in the percentage of misconceptions between male and female students. With result of chi squared test count equal to 0,797 less than chi square 16,92 table value.Â Keywords: description, misconception profile, static electricity